2009
DOI: 10.1007/s11882-009-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of nasal allergy in chronic secretory otitis media

Abstract: Nasal allergy seems to be one of the important causes of chronic secretory otitis media (SOM) in children and adults. Chronic SOM is unequivocally related to disturbed function of the eustachian tube, which facilitates communication of the middle ear with the nasopharynx, nasal cavity, and indirectly with paranasal sinuses. The most serious consequences of chronic SOM are decreased elasticity of the tympanic membrane and hearing impairment. Allergic reactions in the nasal mucosa leading to release of various m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 46 publications
1
24
0
2
Order By: Relevance
“…Theoretically, nasal obstruction due to an allergy can lead to an increase in negative pressure in the nasopharynx, resulting secondarily in decreased Eustachian tube patency, and disturbance of its ciliary epithelial function with subsequent increase in the negative pressure in the middle ear cavity. Several theories have been proposed to explain the Eustachian tube dysfunction caused by allergic inflammation, including retrograde spread of edema, poor mucociliary function, and venous engorgement and hypersecretion of mucus [ 3 ]. It has been suggested that the development of OME is the result of improperly functioning barriers (mucociliary system, immune system, and Eustachian tube) conferring resistance to bacteria [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretically, nasal obstruction due to an allergy can lead to an increase in negative pressure in the nasopharynx, resulting secondarily in decreased Eustachian tube patency, and disturbance of its ciliary epithelial function with subsequent increase in the negative pressure in the middle ear cavity. Several theories have been proposed to explain the Eustachian tube dysfunction caused by allergic inflammation, including retrograde spread of edema, poor mucociliary function, and venous engorgement and hypersecretion of mucus [ 3 ]. It has been suggested that the development of OME is the result of improperly functioning barriers (mucociliary system, immune system, and Eustachian tube) conferring resistance to bacteria [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that the development of OME is the result of improperly functioning barriers (mucociliary system, immune system, and Eustachian tube) conferring resistance to bacteria [ 13 ]. The pathogenesis of OME is related primarily to Eustachian tube dysfunction, including obstruction, abnormal patency, and non-optimally functioning ciliated epithelium [ 3 , 14 ]. These conditions can facilitate the aspiration of nasopharyngeal secretions containing pathogenic bacteria into the middle ear cavity, leading to the development of OME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ribeiro (4) encontró que la adenoidectomía en niños mayores de 10 años fue un predictor independiente de éxito funcional, probablemente debido a la mejor función tubárica. Gamra encontró que la rinitis alérgica fue un factor contribuyente al fracaso de la cirugía (p<0,001), debido tal vez a los mediadores inflamatorios liberados en la mucosa nasal o indirectamente por la obstrucción (29).…”
Section: Discussionunclassified
“…As a consequence, atopy produces allergy with the typical symptoms of asthma, rhino conjunctivitis, or eczema. Atopy has been associated with several ear, nose, and throat (ENT) disorders, such as otitis media with effusion [1][2][3][4], adenoid hypertrophy [5][6][7], rhinitis and sinusitis [8,9], Ménière disease [10][11][12], and Reinke edema [13]. When a patient is referred for one of these common diseases, ENT specialists usually address the existence of an allergic substrate by means of a direct, time-consuming interview or empiric treatments [14].…”
Section: Introductionmentioning
confidence: 99%